Collins COBUILD advanced learner's English dictionary (Glasgow, Great Britain : HarperCollins Publishers, 2006)
The fifth edition of the Collins COBUILD Advanced Learner's English Dictionary offers up-to-date coverage of today's English in a clear, attractive format
Keywords: English language -- Dictionaries; English language -- Usage